Does the motivation and parents involvement affected by distance learning media during pandemic covid 19? - Sujarwo Sujarwo; Erma Kusumawardani; Yuli Nurmalasari (LPMPP Universitas Negeri Yogyakarta, 2022)
The COVID-19 pandemic has been increasing the demand for creative and innovative strategies for early childhood education in achieving adequate educational goals. The present study aimed to empirically find out the effect of the use of tutorial video and children worksheet on preschool children’s motivation and parents’ involvement in accompanying children during study from home period. This research is experimental with a one-group pre-test-post-test experimental design. The population of this study were parents of grade A kindergarten children consisting of 8 kindergarten schools through purposive. Each class consists of 12-20 parents. The research sample consisting of two classes was divided into class A as an experimental group and class B as control group. Data collection using parental involvement and motivation questionnaires, observation, interviews, and documentation. Data analysis used used T-test and analysis of variance (ANAVA) paths. The results showed that there was a significant difference both in parents' motivation and involvement when using children's worksheets and tutorial videos obtained from the results of analysis with ANAVA by the sig. value of 0.01 0.05, which means the using children's worksheets and tutorial videos was enhancing parents' motivation and involvement in assisting children's learning process.